Amino acid composition in common bean cultivars and applications for genetic breeding - Ribeiro, Nerinéia Dalfollo; Londero, Patrícia Medianeira Grigoletto; Filho, Alberto Cargnelutti; Jost, Evandro; Poersch, Nerison Luis; Mallmann, Carlos Augusto (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to determine the amino acid composition of seeds of common bean cultivars and to examine the presence of cultivar x location interactions in amino acid contents, and to identify common bean cultivars for direct consumption or use in breeding programs. The amino acid contents were determinated through high performance liquid chromatography (HPLC), in 19 common bean cultivars obtained in two localities. The mean data sets of each cultivar, in duplication, were compared by the F test at 5% probability for each location. Grains of the common bean cultivars analyzed showed essential and nonessential amino acids contents appropriate for daily supply requirements of human adults, which indicates the high quality of common bean protein. The common bean cultivars were constituted mainly of the following essencial amino acids: leucine, lysine, phenylalanine, valine, isoleucine, threonine, histidine and methionine; and, also, the following nonessencial amino acids: glutamic acid, aspartic acid, arginine, serine, alanine, glycine, tyrosine, proline and cysteine. The leucine, isoleucine, histidine, valine, threonine, glycine and alanine contents were affected by the cultivar x location interactions. Cultivar Iraí presents amino acid content suitable for diet enrichment and germplasm improvement.